PENGARUH INTENSITAS PENGGUNAAN APLIKASI CANVA DALAM PEMBELAJARAN PAI TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA - Ifa Datuzuhriah; Mardiah Astuti; Syarnubi; Muhammad Fauzi; Yulia Tri Samiha (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2026)
This research was motivated by the low motivation and learning outcomes of students in Islamic Religious Education (PAI) subjects at SDN 02 Lubuk Keliat. The learning process was still dominated by conventional methods, and the use of digital media, especially the Canva application, had not been implemented optimally and consistently. This study aimed to determine the intensity of Canva application usage in PAI learning, identify the level of students’ motivation and learning outcomes, and examine the effect of the intensity of Canva application usage on students’ motivation and learning outcomes. This study used a quantitative approach with a causal associative research design. The population consisted of all sixth-grade students at SDN 02 Lubuk Keliat, totaling 40 students, using a saturated sampling technique. Data were collected through questionnaires, learning outcome tests, and documentation. Data analysis employed normality tests, linearity tests, and simple linear regression analysis using SPSS. The results showed that the intensity of Canva application usage had a significant effect on students’ learning motivation with a significance value of 0.049 < 0.05. However, the intensity of Canva application usage did not have a significant effect on students’ learning outcomes with a significance value of 0.312 > 0.05. Therefore, it can be concluded that the use of the Canva application in PAI learning was able to increase students’ learning motivation, but had not significantly affected students’ learning outcomes.